'Iyani, A Shirazi Poet and Historian in the Bahmani Deccan. Issue 2 (3rd July 2021) - Peacock, A.C.S.
ABSTRACT: This paper examines MS D. 92 of the Government Oriental Manuscripts Library, Madras/Chennai, which contains the works of 'Iyani, a late fifteenth century Shirazi poet and historian. 'Iyani had migrated to the Deccan, and wrote in Persian in the Bahmani sultanate (1347–1528), receiving the patronage of both Sultan Mahmud Shah (r. 1482–924) and Habib al-Din Muhibballah, a descendant of the Sufi saint Shah Ni'matallah Vali of Kirman. The paper investigates 'Iyani's works, which comprise qasida s, ghazal s, ruba'iyyat and two mathnavī s, the Jangnama-i Shahrukh and the Fathnama-i Mahmud Shahi . The latter, recording the defeat of a rebellion led by the Abyssinian commander in Gulbarga, Dastur Dinar, sheds new light on the political and factional environment in the final stages of Bahmani rule. 'Iyani's works represent a new source for the cultural, literary and political history of the fifteenth century Deccan.